Livestock management and automation system using radio waves - Aris, Ishak; Tengku Muda Mohamed, Mahmud; Ziabari Khoshgoftar, Seyedeh Saeedeh; Hassan, Azmi; Mohd Shariff, Saibi (2013)
The present invention provides a muitiband radio frequency identification-based embedded system (100) for livestock management and automation system, in which an animal carries a passive radio frequency identification (RFID) tag. The system comprises an automation means (102) that is adopted to control and monitor equipments in a house of the tagged animal; an animal detection means (101 ) to identify and monitor animals when entering the RFID coverage range; a server (103) to save data of the animals received from the animal detection means (101) and automation system (102); and an internet connection (104) to send the data to a user (105).